2013
DOI: 10.1007/s10554-013-0266-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of atherosclerosis in the descending thoracic aorta with coronary artery disease on multi detector row computed tomography coronary angiography in patients with suspected coronary artery disease

Abstract: The association between atherosclerosis in the descending thoracic aorta (DTA) visualized on computed tomography coronary angiography (CTA) and coronary artery disease (CAD) has not been extensively explored. Therefore, a comprehensive analysis of DTA atherosclerosis on CTA was performed and the association of DTA atherosclerosis with CAD was evaluated in patients with suspected CAD. A total of 344 patients (54 ± 12 years, 54% men) with suspected CAD underwent CTA. CTA were classified based on CAD severity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…[3132] In an autopsy series of abdominal aortic plaques, it was reported that plaques in the abdominal aorta were more severe in patients with cardiac injury compared to those without. [33] The presence and severity of plaques at the descending thoracic aorta were independently related to significant coronary artery disease detected by a coronary angiography CT.[34] Coronary calcification was found to be associated with carotid plaques. [35] Kälsch et al .…”
Section: Discussionmentioning
confidence: 99%
“…[3132] In an autopsy series of abdominal aortic plaques, it was reported that plaques in the abdominal aorta were more severe in patients with cardiac injury compared to those without. [33] The presence and severity of plaques at the descending thoracic aorta were independently related to significant coronary artery disease detected by a coronary angiography CT.[34] Coronary calcification was found to be associated with carotid plaques. [35] Kälsch et al .…”
Section: Discussionmentioning
confidence: 99%
“…6 Herein, calcification process in great vessels (aorta) and coronary vessels proceeds independently of each other. 7 The differentiation between smooth and hard plaque structures remains reasonable because its vulnerability represents the risk for a myocardial infarction or complete vascular occlusion. Plaque morphology and composition play critical roles in plaque rupture and coronary occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…A lesão apresentada na Figura 4 (a) é caracterizada pela presenc ¸a de um estreitamento visível e é responsável pelo melhor resultado do DeepCADD na comparac ¸ão com os especialistas. Nesse mesmo aspecto de lesões, o DeepCADD foi capaz de identificar as lesões < 30%, conhecidas como irregularidades parietais que normalmente não são selecionadas pelos especialistas devido a sua baixa significância na reduc ¸ão de fluxo sanguíneo [Roos et al 2013]. Por outro lado, as lesões apresentadas na Figura 4 (b) e Figura 4 (c) foram as responsáveis pela maior parte de falso-negativos, por dois principais motivos.…”
Section: Validac ¸ãOunclassified